An experimental study on the interface mass transfer governing thermodynamics of stored liquids - Rakshit, D.; Narayanaswamy, Ramesh; Truong, T.; Thiagarajan, K. (Research Publishing Services, 2010)
Heat transfer processes that occur in mixtures of more than one substance always deals with mass transfer phenomenon. The thermodynamics of two phase physics involving different liquid-gas combinations can be studied under the regime of these conjugate heat and mass transfer phenomena. Evaporation from liquid surface depends on: (i) liquid-vapor interfacial temperature, (ii) fractional concentration of the evaporating liquid present in gaseous state, and (iii) the surface area of the liquid vapor interphase. With increasing demand for Liquefied Natural Gas (LNG), transportation of LNG through ships is in high demand with even low filling levels. This type of transportation is prone to sloshing due to ship motion in a seaway. The ullage pressure above the liquid containment plays a critical role in making a proper selection of the various fill levels and temperatures with which LNG can be transported from one place to another. Multiphase characteristics of LNG may be understood by examining a miscible fluid combination viz. water-vapor water system. In particular, the roles played by vibration in the heat transfer mechanisms such as boil-off during heating and condensation when in direct contact with the atmosphere, needs to be understood. In the present study an attempt has been made to understand the underlying principle of an evaporating and condensing system involving two-phase heat and mass transfer by studying its effect on a stationary liquid tank.An experiment with an air-water system has been designed and conducted to explain the characteristics of heat and mass transfer at various fill levels and temperatures. The sophistication lies in the instrumentation of the experiment where conductivity probes accompanied by a humidity meter is used in combination with thermocouples and ullage pressure measuring device to map the entire physics of interface mass transfer. This is followed by an estimation of overall mass transfer from the interface in analogy with the multiphase heat transfer taking place across the interphase.